A Rare Case Report of Serous Cystadenoma with Coexisting Sclerosing Stromal Tumor of Ovary - Kalita, Lachit; Kalita, Abhijit; Harlalka, Munmun (Annals of Pathology and Laboratory Medicine, 2023)
Various forms of collision tumors have been reported in literature before. Ovarian tumors also exhibit different histological components at times. The epithelial neoplasm of ovary in coexistence with sertoli leydig cell tumor, granulosa cell tumor, cystic teratoma and stromal tumor with minor sex cord elements are known to exist. However, literature related to association of serous neoplasm of ovary with sclerosing stromal tumor is not known. We report a case of serous cystadenoma with coexisting sclerosing stromal tumor in a 31-year-old lady which is probably one of the first case reports of such a combination till date.